PRELIMINARY STUDY OF MICRODEBRIS CONTAMINATION IN SEDIMENT FROM THREE ESTUARIES ON THE PANGKAJENE RIVER - Sukri, Nurul Magfirah; Ambeng, Ambeng; Ilham, Ilham; Tanjung, Jennyta Dhewi Darmansyah; Anshari, Muhammad Al; Kuswanto, Hedi; Zainuddin, Zarlina (Jurnal Ilmu Kelautan SPERMONDE, 2022)
Studies on microdebris contamination in sediments at the estuary of the Pangkajene River were carried out at three stations. This study aims to observe the abundance and characteristics of microdebris in the estuary sediments of the Pangkajene River. The samples of sediment were collected using a core sampler with a diameter of 8 cm. Microdebris was extracted using the flotation method and vacuum filtration system. The particles were observed with a stereomicroscope then classified based on shape (form), size, and color. The number of particles found ranged from 2.83±2.04-4.00±1.87 item/100gr. The analysis of variance (ANOVA) showed p>0.05, therefore the abundance of microdebris between the three stations did not show a significant difference. Microdebris in Fragment form had the highest percentage compared to fibers and granules. Blue and black particles of microdebris were the most common colors. The dominant size of particles was found in the size class <100µm and 100µm-500µm. This preliminary study revealed that the microdebris occurs in the Pangkajene estuary sediments. Currently, we have not classified the types of microdebris found as microplastic, semi-synthetic debris, or natural origin. Therefore, further research is needed to verify particles using an FT-IR Microscope to determine the type of microdebris polymer.